2008
DOI: 10.1590/s1678-77572008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and delayed solubility of mineral trioxide aggregate and Portland cement

Abstract: This study investigated the solubility of mineral trioxide aggregate (MTA) and Portland cement since its mixture until 672 hours, by means of two complimentary methods. Metal ring molds filled with the cements were covered with distilled water and, at each experimental time (3, 24, 72, 168, 336 and 672 hours), were weighed as soon as the plates in which the samples have been placed. Empty rings served as the control group (n=8). Mean weight gain and loss was determined and analyzed statistically by two-way ANO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 28 publications
(72 reference statements)
1
39
0
3
Order By: Relevance
“…The level of solubility was less than 3% and thus within the limits set by international standards (1). The higher solubility of MTA is in accordance with previous research in which MTA exhibited higher solubility than Portland cement (7,18). The solubility of MTA was higher than the 3% recommended by ISO 6867; 2002 (1).…”
Section: Discussionsupporting
confidence: 90%
“…The level of solubility was less than 3% and thus within the limits set by international standards (1). The higher solubility of MTA is in accordance with previous research in which MTA exhibited higher solubility than Portland cement (7,18). The solubility of MTA was higher than the 3% recommended by ISO 6867; 2002 (1).…”
Section: Discussionsupporting
confidence: 90%
“…In an investigation on the solubility of AMTA in comparison to PC, the former material showed more than a 3% weight loss during the first 24 hours after mixing, which is beyond acceptable weight loss determined by the International Standard Organization (72).…”
Section: Effect Of the Methods Of Placement On Mta Physical Propertiesmentioning
confidence: 71%
“…Other reasons for difference in MTA solubility include the time of immersion of the material, the type of MTA, and the powder-to-liquid ratio (42,46,71,72).…”
Section: Solubilitymentioning
confidence: 99%
“…It is suggested that at least 72 hours are necessary to achieve the desirable sealability of MTA (30,31). Odabas et al (16) evaluated the SBS of composite to Biodentine after 2 time intervals (ie, 12 minutes and 24 hours) and obtained an increased SBS value for the 24-hour period.…”
Section: Discussionmentioning
confidence: 99%